2022
DOI: 10.3389/pore.2022.1610293
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Potential Prognostic Value of SOX9, MCL-1 and SPOCK1 in Gastric Adenocarcinoma

Abstract: Gastric cancer is a common malignancy and remains one of the leading causes of cancer-related deaths, though its incidence is in decline in most developed countries. One of the major challenges of treating gastric cancer is tumor heterogeneity, which portends a high degree of prognostic variance and the necessity for different treatment modalities. Tumor heterogeneity is at least in part due to divergent differentiation of tumor cells to clones harboring different molecular alterations. Here we studied the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the MCL-1 protein is involved in the occurrence and development of tumors. It has been reported that amplification of the MCL-1 gene and an increase in MCL-1 protein expression levels are common in various types of tumor cells, such as breast, prostate and lung cancer cells (34)(35)(36)(37)(38). In addition, high MCL-1 expression levels lead to the resistance of tumor cells to chemotherapeutic drugs (39).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the MCL-1 protein is involved in the occurrence and development of tumors. It has been reported that amplification of the MCL-1 gene and an increase in MCL-1 protein expression levels are common in various types of tumor cells, such as breast, prostate and lung cancer cells (34)(35)(36)(37)(38). In addition, high MCL-1 expression levels lead to the resistance of tumor cells to chemotherapeutic drugs (39).…”
Section: Discussionmentioning
confidence: 99%